Abu Bakr Effendi: a report on the activities and challenges of an Ottoman Muslim theologian in the Cape of Good Hope - Genço?lu, Halim (Department of Religious Studies, 2014)
This thesis presents the religious activities of an Ottoman Islamic scholar Abu Bakr Effendi and his educational challenges at the Cape of Good Hope. Abu Bakr Effendi was a professor of canon law who was sent to the Cape by the Ottoman Caliph in order to resolve the religious issues as well as educate the Muslims in South Africa in the second half of the nineteenth century. This study takes into consideration diverse archival materials that explain different dimensions of the socio-historical events which happened during Effendi's stay in South Africa. Due to limited reliable sources, Effendi's activities have not been examined by researchers extensively. Several local newspapers, South African and Ottoman archival materials not used before in such studies, private family documents, foundation (Waqf) records and official correspondences have been used in this study and contributed to understanding the social-religious situation amongst Muslims at the Cape of the nineteenth century. Applying a comparative historical method, the study shows how Effendi became a prominent scholar in society despite his reformist understanding with regards to Islamic topics which made him a marginal theologian in the eyes of local Muslims. In this sense, the study illustrates the contribution of his works in the Muslim social sphere and how it enabled the emergence of a Muslim consciousness and identity in Southern Africa. Finally, with his cultural and educational endeavors, Effendi became a historical figure in South African society and this reality has been illuminated by rich archival documents.